Studies on formation of the radially-directed electron beam generated by the magnetron gun with a secondary emission cathode - Ayzatsky, M.I.; Dovbnya, A.N.; Mazmanishvili, A.S.; Reshetnyak, N.G.; Romas’ko, V.P.; Chertishchev, I.A. (Вопросы атомной науки и техники, 2016)
Results are reported from the experimental and model investigations of the formation of a radially-directed electron beam, which is generated by a secondary-emission cathode magnetron gun in the electron energy range between 30 and 65 keV, as the beam is transported in the decreasing magnetic field of the solenoid. The beam transport was realized in the system consisting of copper rings with an internal diameter of 66 mm; the system was at a distance of 85 mm from the magnetron gun edge. The radial beam current and its distribution along the length of the measuring ring system were investigated versus the amplitude and gradient of the magnetic field. Studies were made into the mode of electron current bunch formation. Numerical simulation data on the tubular electron flux motion in the decreasing magnetic solenoidal field are presented.